2015
DOI: 10.3892/mmr.2015.4696
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA promotes the proliferation of WB-F344 hepatic oval cells via Wnt/β-catenin signaling

Abstract: Tanshinone IIA (TSA) is a widely used traditional Chinese medicine, which has been demonstrated to protect damaged liver cells and is currently administered in the treatment of liver fibrosis. Liver precursor cells, also termed oval cells, are key in the repair of liver tissues following injury. However, whether TSA improves the function of liver cells and protects the liver from injury by enhancing the growth and proliferation of hepatic oval cells remains to be elucidated. In the present study, low to modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…e prescription consists of several traditional Chinese herbal medicines, such as Astragalus membranaceus, Salvia miltiorrhiza, red peony root, Poria, radix curcumae, and Amomum cardamomum. Tanshinone IIA is an extract from the sage plant, Salvia miltiorrhiza, which has been reported to increase the proliferation of WB-F344 hepatic oval cells by activating canonical Wnt signaling pathway [8]. Astragaloside IV, extracted from the traditional Chinese medicine Astragalus membranaceus, has been extensively tested and proved to be effective for antifibrosis [9] and metastasis suppression in hepatoma cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…e prescription consists of several traditional Chinese herbal medicines, such as Astragalus membranaceus, Salvia miltiorrhiza, red peony root, Poria, radix curcumae, and Amomum cardamomum. Tanshinone IIA is an extract from the sage plant, Salvia miltiorrhiza, which has been reported to increase the proliferation of WB-F344 hepatic oval cells by activating canonical Wnt signaling pathway [8]. Astragaloside IV, extracted from the traditional Chinese medicine Astragalus membranaceus, has been extensively tested and proved to be effective for antifibrosis [9] and metastasis suppression in hepatoma cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Rationale for examining Wnt/β-catenin signaling pathway in our heteroprotection model of hepatotoxicity is that, (1) pro-regenerative cyclin D1 is a target gene for β-catenin signaling pathway 55 and (2) activation of β-catenin signaling through endogenous and pharmacological interventions caused compensatory liver regeneration. 17 - 19 Moreover, Wnt/β-catenin was recently shown to exert antioxidant and mitochondrial protective effects during ischemia reperfusion liver injury. 21 In our studies, we found early and robust activation of β-catenin pathway as indicated by overexpression of total and activated β-catenin in the TA + APAP-treated mice compared to the DW + APAP-treated mice ( Figure 4A and 4B ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the underlying machineries for tissue regeneration after toxicant-induced and traumatic organ injuries (liver, kidney, lung, heart, and axon). 7 , 11 - 16 Of these cytokine-, chemokine-, growth factor-, neuroendocrine-, mitogenic pathway-, and stem cell-based mechanisms of various organs regeneration, canonical Wnt/β-catenin signaling pathway appears a highly promising one for liver regeneration due to the following compelling evidences: (1) of the several hepatic mitogenic pathways studied, only Wnt/β-catenin pathway was directly correlated with liver regeneration after the APAP treatment 17 ; (2) stimulation of Wnt/β-catenin pathway using a synthetic compound tanshinone IIA stimulated rat hepatic oval cells proliferation, 18 which often contributes toward liver regeneration 19 ; (3) prior treatment with a Wnt/β-catenin agonist reversed the inhibited hepatocyte proliferation in the small-for-size liver graft model in Sprague-Dawley rats 20 ; and (4) Wnt/β-catenin pathway can also protect the liver against oxidative injury by preserving mitochondrial functions. 21 These observations highlight the need to further examine the role of the hepatic Wnt/β-catenin signaling to better understand the toxicodynamics of autoprotection and heteroprotection models of hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that the elevation of Cys-C can evoke an inhibition of cathepsin B, and an accumulation of collagen I, collagen III and fibronectin in the ischaemic area of the myocardium, indicating a stimulatory role of Cys-C in cardiac hypertrophy [ 34 ]. Additionally, the activation of Wnt signaling pathway is responsible for the growth of hypertrophy [ 8 , 35 , 36 ]. After treated by tanshinone IIA, the Cys-C and Wnt expressions decreased significantly, suggesting that tanshinone IIA may have a protective effect on cardiac hypertrophy in SHRs through the inhibition of the Cys-C/Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%